2019
DOI: 10.1177/1071181319631457
|View full text |Cite
|
Sign up to set email alerts
|

Performance in Noise: The Relationship Between Workload And Situation Awareness in Navy Tactical Teams

Abstract: The relationship between workload and situation awareness (SA) has been researched generally; however, the relationship between measures of SA and workload, SPAM and NASA TLX respectively, has not been established. This study was completed using a tactical military scenario in which two participants acted as they would standing watch on a US Navy ship. One participant, the Tactical Action Officer (TAO) had reduced speech intelligibility in some trials. The results showed that the relationship between workload … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They also found that verbal confirmation responses containing inaccurate information did not begin to occur until the MRT score dropped below 80%. In a later study, they also found that reduced speech intelligibility on the MRT for one member of the team led to increased task load for other crew members in the CIC even when they were able to hear normally (Holthausen et al 2019).…”
Section: Experimental Validationmentioning
confidence: 96%
“…They also found that verbal confirmation responses containing inaccurate information did not begin to occur until the MRT score dropped below 80%. In a later study, they also found that reduced speech intelligibility on the MRT for one member of the team led to increased task load for other crew members in the CIC even when they were able to hear normally (Holthausen et al 2019).…”
Section: Experimental Validationmentioning
confidence: 96%